A NEW DINOSAUR TRACKSITE IN THE LATE ALBIAN OF ISTRIA, CROATIA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
A new site with dinosaur footprints has been found in the upper Albian sediments of Istria, Croatia. The site was discovered near the city of Pula, at the Zlatne Stijene locality. The carbonate succession of the Zlatne Stijene locality is characterized by thin bedded limestones deposited in peritidal and foreshore environments. The microfossil assemblage found at the site indicates a late Albian age. One clearly distinguishable footprint and four indeterminate rounded tracks were discovered at the investigated outcrop. The footprint is tridactyl and belongs to a medium-sized bipedal theropod dinosaur of approximately 3 meter in length. Regarding dimensions and morphology it is closely related to the other late Albian theropod footprints from the Adriatic-Dinaridic carbonate platform (ADCP). The Zlatne Stijene locality fits with the Brontopodus ichnofacies concept.
Keywords: Dinosaur footprints; Theropods; late Albian; Istria; ADCP